Arbitrary pattern formation by opaque fat robots on infinite grid. Issue 5 (3rd September 2022) - Kundu, Manash Kumar; Goswami, Pritam; Ghosh, Satakshi; Sau, Buddhadeb
ABSTRACT: Arbitrary Pattern formation ( A P F ) by a swarm of mobile robots is a widely studied problem in the literature. Many works regarding A P F have been proposed on plane and infinite grid by point robots. But in practical application, it is impossible to design point robots. In Bose et al. [Arbitrary pattern formation on infinite grid by asynchronous oblivious robots. Theor Comput Sci. 2020;815:213–227], the robots are assumed opaque fat robots but the environment is plane. To the best of our knowledge, no work till now ever considered the A P F problem assuming opaque fat robots on infinite grid where movements are restricted. In this paper, we have provided a collisionless distributed algorithm and solved A P F using 9 colours.